Assessment of rural development programmes to enhance youth integration - Thomas Dax; Ingrid Machold (European Regional Science Association (ERSA), 2001)
In recent years concern about social exclusion processes has reached also rural areas. The rising unemployment and the limited opportunities for young people have turned the attention of policy analysis to this social group and to processes of social exclusion under these specific regional conditions. The results presented are drawn from the EU-project “Policies and young people in rural development” under the 4th Framework programme (FAIR6 CT-98-4171) where different aspects of economic and social integration/exclusion of young people in rural areas and their recognition in rural development programmes of the EU has been analysed. The paper focuses on the scope to enhance the aspect of young people integration in rural/regional programmes. To this end, it starts with a presentation of the policy background and its evaluation, particularly with regard to its rising priority over the last EU-reforms. It continues with the investigation of selected exemplary cases of policy measures and initiatives specifically addressing young people in rural development provided by the seven project partners study areas. The concluding part draws on evaluation studies on rural development programmes all over the European Union with regard to youth participation and explores the scope for future strengthening of respective activities and inclusion of young people concerns in rural development programmes. Experiences from this analysis suggests that with fundamental changes in the market structures and relations programmes targeted at specific rural areas cannot neglect the emerging interrelations to other areas. Hence a rural policy addressing the needs of young people has to address directly its insertion into the regional framework and its relation to regional policy. (Paper for conference theme "Socio-economic cohesion and regional/local development", thematic area %22Socio-economic exclusion")
Keywords: 330